2022
DOI: 10.3390/nu14030706
|View full text |Cite
|
Sign up to set email alerts
|

Differential Glycemic Effects of Low- versus High-Glycemic Index Mediterranean-Style Eating Patterns in Adults at Risk for Type 2 Diabetes: The MEDGI-Carb Randomized Controlled Trial

Abstract: A Mediterranean-style healthy eating pattern (MED-HEP) supports metabolic health, but the utility of including low-glycemic index (GI) foods to minimize postprandial glucose excursions remain unclear. Therefore, we investigated the relative contribution of GI towards improvements in postprandial glycemia and glycemic variability after adopting a MED-HEP. We conducted a randomized, controlled dietary intervention, comparing high- versus low-GI diets in a multi-national (Italy, Sweden, and the United States) sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Glycemic variability, measured as the coefficient of variation (%CV), over four weekdays was significantly lower during the low-GI/SFA diet when compared to the high-GI/SFA diet. This finding is in line with previous studies showing that a higher-glycemic-index diet significantly increased glycemic variability [ 34 , 35 ]. Monitoring glycemic variability was also a good way to check participants’ adherence to the diet, and our findings confirm that participants indeed adhered to the high-GI or low-GI diets.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Glycemic variability, measured as the coefficient of variation (%CV), over four weekdays was significantly lower during the low-GI/SFA diet when compared to the high-GI/SFA diet. This finding is in line with previous studies showing that a higher-glycemic-index diet significantly increased glycemic variability [ 34 , 35 ]. Monitoring glycemic variability was also a good way to check participants’ adherence to the diet, and our findings confirm that participants indeed adhered to the high-GI or low-GI diets.…”
Section: Discussionsupporting
confidence: 93%
“…This was especially apparent after lunch ( p < 0.05; Figure 2 C). This is in line with findings from Bergia et al [ 34 ] who reported seeing more robust differences in glycemia between a high- vs. low-GI meal test after the lunch meal when compared to the breakfast.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the non-pregnancy literature, efficacy of dietary interventions has been reported to differ for patients with distinct metabolic profiles, for example high fasting glucose vs high fasting insulin, or insulin resistance vs low insulin secretion [73][74][75] . More recent evidence from appropriately designed, prospective dietary intervention studies has confirmed that dietary interventions tailored towards specific metabolic profiles have more beneficial effects than interventions not specifically designed towards a patient's metabolic profile [76][77][78][79] . Ongoing studies such as the Westlake Precision Birth Cohort (WeBirth) in China (NCT04060056) and the USA Hoosier Moms Cohort (NCT03696368) are collecting additional biomarkers which will enhance knowledge in this field.…”
Section: Discussionmentioning
confidence: 99%
“…It also affects inflammatory markers such as hs-CRP ( 54 , 56 ). GI, another CQI component, was shown to increase postprandial glucose, insulin responses, TG, and non-HDL cholesterol, and decrease HDL cholesterol ( 60 , 61 ). Whole grains are one of the CQI components that in previous studies was shown to have significant effects on HDL, LDL, TC, HbA1c, and CRP ( 62 ).…”
Section: Discussionmentioning
confidence: 99%